Multimodality Discourses Of The Miss Universe Beauty Pageant As An Arena Of Cultural Production - HERMAWAN, Dony; RONDA, Andi Mirza; SIGIT, Ridzki Rinanto (International Journal of Environmental, Sustainability, and Social Science, 2023)
The Miss Universe beauty pageant is a cultural production arena where the construction of female beauty is formed through an ideal image that is slowly socialized by the media, becoming a standard in society. This research aims to find out and describe the construction of the meaning of beauty built through the Miss Universe beauty contest through the perspective of Discourse Analysis Multimodality, reveal the implied meaning of gestures, and understand the self-identity of the Miss Universe contestants. This qualitative research uses a critical paradigm using document studies, interviews, and literature. Data analysis used multimodality discourse analysis through data reduction, presentation, and conclusion. The results of this study indicate that: 1) The meaning of beauty at the Miss Universe 2021 pageant is constructed through the depiction of the contestants' perfection, which consists of their physique, attitude, and insight. The contestants' appearances have created beauty criteria that shape the idealization of the female figure and influence the audience's perspective on self-appreciation; 2) Overall, the most frequently shown contestant gestures give confidence and grace according to the message in the Miss Universe slogan, namely confidently beautiful; 3) The identity of the Miss Universe contestants reveals who, personality, where, and what culture is being performed with various styles and uniqueness. This uniqueness can be in the form of personality, interests, favorite food, way of talking, way of walking, and even how the contestants behave when responding to things and questions.